HIV-1 Vpr triggers natural killer cell-mediated lysis of infected cells through activation of the ATR-mediated DNA damage response. - Jeffrey Ward; Zachary Davis; Jason DeHart; Erik Zimmerman; Alberto Bosque; Enrico Brunetta; Domenico Mavilio; Vicente Planelles; Edward Barker (PLoS Pathogens)
Natural killer (NK) cells are stimulated by ligands on virus-infected cells. We have recently demonstrated that NK cells respond to human immunodeficiency virus type-1 (HIV-1)-infected autologous T-cells, in part, through the recognition of ligands for the NK cell activating receptor NKG2D on the surface of the infected cells. Uninfected primary CD4(pos) T-cell blasts express little, if any, NKG2D ligands. In the present study we determined the mechanism through which ligands for NKG2D are induced on HIV-1-infected cells. Our studies reveal that expression of vpr is necessary and sufficient to elicit the expression of NKG2D ligands in the context of HIV-1 infection. Vpr specifically induces surface expression of the unique-long 16 binding proteins (ULBP)-1 and ULBP-2, but not ULBP-3, MHC class I-related chain molecules (MIC)-A or MIC-B. In these studies we also demonstrated that Vpr increases the level of ULBP-1 and ULBP-2 mRNA in primary CD4(pos) T-cell blasts. The presence of ULBP-1 and ULBP-2 on HIV-1 infected cells is dependent on the ability of Vpr to associate with a protein complex know as Cullin 4a (Cul4a)/damaged DNA binding protein 1 (DDB1) and Cul4a-associated factor-1(DCAF-1) E3 ubiquitin ligase (Cul4a(DCAF-1)). ULBP-1 and -2 expression by Vpr is also dependent on activation of the DNA damage sensor, ataxia telangiectasia and rad-3-related kinase (ATR). When T-cell blasts are infected with a vpr-deficient HIV-1, NK cells are impaired in killing the infected cells. Thus, HIV-1 Vpr actively triggers the expression of the ligands to the NK cell activation receptor.